Glimpsing “The Architect” in the daily work of nurses in hospital management - Ludmila Mourão Xavier-Gomes; Gizele Ferreira David; Hanna Beatriz Bacelar Tibães; Susiane Sucasas Frison; Thiago Luis de Andrade-Barbosa (O Mundo da Saúde)
This study aimed at understanding the daily work of nurses in managerial practice in medium-sized hospitals, based on working process proposed by the architect Richard Sennet. This is a qualitative descriptive study was conducted through a case study whose scenario consisted of four medium size hospitals in a city located in the northern region of Minas Gerais. Data collection was conducted through semi-structured interviews with twelve nurses in management positions in strategic and intermediate levels of a hospital organization. Study participants were 12 nurse managers that met the established inclusion criteria. Data were submitted to content analysis, and the study uncovered four empirical categories operationalized in three stages: pre-analysis, material exploration and treatment of results and interpretation. The analysis showed the following empirical categories, “the nurse in the search for quality of care,” “leadership as essential skill of the nurse manager” and “the formation of the nurse for the exercise of the managerial function. The results showed that nurse managers have interest and concern for the quality of care, vision of leadership as a key component in working relationships and communication. In addition, they stressed the importance of academic training for the performance of management functions and everyday practices in this function. We conclude that nurse managers understands their importance in the hospital, seeing themselves as professionals and experts of labor and administrative relationships, proposing strategies to achieve a planned care with a higher quality.